2018
DOI: 10.1556/004.2018.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methionine deficiency on oxidative stress and apoptosis in the small intestine of broilers

Abstract: The aim of this study was to investigate the effects of methionine (Met) deficiency on antioxidant functions (in the duodenal, jejunal and ileal mucosa) and apoptosis in the duodenum, jejunum and ileum of broiler chickens. A total of 120 one-day-old Cobb broilers were divided into two groups and fed a Metdeficient diet and a control diet, respectively, for six weeks. The activities of superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GSH-Px), the ability to inhibit hydroxyl radicals, and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 37 publications
0
9
1
Order By: Relevance
“…Additionally, contrary to our results, study of Ruan et al showed that methionine deficiency led to oxidative stress in the small intestine of broilers (Ruan et al 2018). The explanation for the protective effect of methionine lies in the fact that methionine residues may have antioxidant properties, protecting the molecules where they are located.…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, contrary to our results, study of Ruan et al showed that methionine deficiency led to oxidative stress in the small intestine of broilers (Ruan et al 2018). The explanation for the protective effect of methionine lies in the fact that methionine residues may have antioxidant properties, protecting the molecules where they are located.…”
Section: Discussioncontrasting
confidence: 99%
“…Also, Jankowski, et al (27) reported that increasing methionine level in broiler diets resulted in a significant increase in glutathione concentration and decreasing both malondialdehyde and plasma triglycerides levels. Furthermore, Ruan, et al (28) reported that 120 one day old broilers supplemented with methionine deficient diet resulted in decreasing SOD, catalase and glutathione peroxidase. Similarly, Wang, et al (29) reported that adding L. carnitine at a dose of 100 mg/kg to broilers diet decreased MDA level in heart tissue, triglycerides content and increased SOD and GR.…”
Section: Effect Of the 4 Supplements On Alt And Astmentioning
confidence: 99%
“…Mou et al (2020b) fed organic selenium to pregnant sows and found this significantly increased the activity of GSH-Px in the serum and placenta of the sows, and significantly decreased the content of MDA (Mou et al, 2020b). Other studies showed that the activity of GSH-Px in the duodenum, jejunum, and rectum of chicks fed Se-deficient diets were significantly lower than those in basal diets (Ruan et al, 2018). The present study showed that HMSEBA significantly increased the activities of GSH-Px, T-SOD, and CAT in the thymus, jejunum, ileum, and colon of gilts, and the content of MDA in each tissue showed a decreasing trend.…”
Section: Discussionmentioning
confidence: 92%